2020
DOI: 10.4102/sajpsychiatry.v26i0.1526
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and clinical correlates of substance use amongst acute psychiatric inpatients in Gauteng, South Africa

Abstract: Background Mental disorders and substance use disorders (SUD) commonly occur together, impacting healthcare outcomes. The diagnosis of substance use is often inadequate when comorbidity is present. It is vital to understand the prevalence of substance use amongst psychiatric patients to inform both clinical practice and service development in South Africa. Aim To ascertain the prevalence and clinical correlates of SUD amongst acute psychiatric inpatients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 41 publications
0
3
1
Order By: Relevance
“…The percentage of participants that reported receipt of disability grant (57%) was higher than the percentage reported in previous studies of mental healthcare users in South Africa [ 26 , 27 ]. Unlike previous research, this study only included participants with a diagnosis of schizophrenia, who may be more likely to qualify for receipt of disability benefits than other mental health care users.…”
Section: Discussioncontrasting
confidence: 62%
“…The percentage of participants that reported receipt of disability grant (57%) was higher than the percentage reported in previous studies of mental healthcare users in South Africa [ 26 , 27 ]. Unlike previous research, this study only included participants with a diagnosis of schizophrenia, who may be more likely to qualify for receipt of disability benefits than other mental health care users.…”
Section: Discussioncontrasting
confidence: 62%
“…Future studies need to explore this finding of selective cocaine use among unemployed and student, however it can be speculated that as previous studies indicated, cocaine may serve as better substance for the group to cope with the anxiety and depression commonly associated with unemployment as also revealed by Tindimwebwa et al 12 Lack of association between other substances and employment status is in contrast to another study, which found that this outcome might be due to a convoluted interaction in which mental illness raises the risk of unemployment, while unemployment raises the risk of mental disease. 45 In contrast, a study done in Nigeria reported that substance use disorder is more common amongst those who are employed. 50 Our study was conducted in a different set up with a different culture.…”
Section: Discussionmentioning
confidence: 94%
“…Marital status was not associated with SUDs in contrast to the previous studies. 12,45 The possible explanation for lack of association is that this study had majority of young and single participants, hence the difficulty to obtain and compare with other marital status. Previous studies have alluded that single people have no familial responsibilities or romantic ties, and for that reason, they tend to have more disposable income to use on different substances.…”
Section: Discussionmentioning
confidence: 96%
“…58 Several studies have reported that comorbid substance use is also associated with long-term benzodiazepine use. 9 , 20 , 22 A South African study 59 reported a high prevalence rate of substance use disorders in psychiatric patients; however, no studies reported an association between comorbid substance use and prolonged benzodiazepine use. Our research found that most patients (80%) had no comorbid substance use disorder, similar to Aragaines et al 53 This may be because of the patients’ under-reporting, poor documentation by the doctors, or small sample size.…”
Section: Discussionmentioning
confidence: 99%